Association of Myeloid Cells of Triggering Receptor-1 with Left Ventricular Systolic Dysfunction in BALB/c Mice with Sepsis - Gaosheng Zhou; Lijun Ye; Liang Zhang; Liangqing Zhang; Yuanli Zhang; Liehua Deng; Huaguo Yao (Hindawi Limited, 2014)
Objective. To investigate the correlation between TREM-1 and LPS-induced left ventricular systolic dysfunction in BALB/c mice. Methods. Male BALB/c mice were randomly divided into 3 groups: LPS, LPS/TREM-1, and control groups which were injected intraperitoneally with 25 mg/kg LPS, 5 μg TREM-1mAb 1 h after LPS challenge, and sterilized normal saline, respectively. Left ventricular systolic function was monitored by echocardiography at 6 h, 12 h, and 24 h. Meanwhile, TNF-α, IL-1β, and sTREM-1 in serum and myocardium were determined by ELISA or real-time PCR; at last left ventricles were taken for light microscopy examination. Results. FS and EF in LPS/mAbTREM-1 group, significantly declined compared with LPS and control group at 12 h, were accompanied with a markedly increase in serum IL-1β (at 6 h) and sTREM-1 (at 12 h and 24 h) expression. Myocardium TNF-α (at 6 h and 24 h) and sTREM-1 (at 6 h) were significantly higher in LPS/mAbTrem-1-treated mice than in time-matched LPS-treated mice; meanwhile myocardium TNF-α mRNA were markedly increased in comparison with LPS-treated or saline-treated mice at 24 h. Besides, mAbTREM-1 aggravated LPS-induced myocardial damage was observed. Conclusions. Our results suggest that TREM-1 is significantly associated with LPS-induced left ventricular systolic dysfunction in BALB/c mice.